2020
DOI: 10.1002/adem.202000669
|View full text |Cite
|
Sign up to set email alerts
|

Impact Behavior of Additively Manufactured Stainless Steel Auxetic Structures at Elevated and Reduced Temperatures

Abstract: Metamaterials produced using additive manufacturing represent advanced structures with tunable properties and deformation characteristics. However, the manufacturing process, imperfections in geometry, properties of the base material as well as the ambient and operating conditions often result in complex multiparametric dependence of the mechanical response. As the lattice structures are metamaterials that can be tailored for energy absorption applications and impact protection, the investigation of the couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The effect was the most profound for the FD version where a significant stress increase between the individual strain rates was observed. This behaviour has been reported for similar cellular structures manufactured from the same material [30,33]. •…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The effect was the most profound for the FD version where a significant stress increase between the individual strain rates was observed. This behaviour has been reported for similar cellular structures manufactured from the same material [30,33]. •…”
supporting
confidence: 83%
“…The DIC procedure was used to evaluate the displacements of selected nodes in the lattice structures. To reveal the anticipated auxetic behaviour and its magnitude, the area difference parameter D A was evaluated according to the definition presented in [33]. The value of D A corresponds to…”
Section: Digital Image Correlationmentioning
confidence: 99%
“…Typically, the X-ray tube was operated with an output power of 1 500 W, although its maximum output power rating is 1 800 W. The tube has, however, a limited lifetime at the maximum output power and therefore most of the imaging was performed at the maximum continuous power settings. Several objects representing typical specimens for impact dynamic experiments were irradiated, namely: closed-cell aluminium foam (cylinder with approximate dimensions of 60 mm in diameter and 30 mm in height, or larger integral blocks), additively manufactured stainless steel auxetic lattice filled with a polymeric filling (cube with approximate dimensions of 12 × 12 × 12 mm 3 ), additively manufactured aluminium alloy auxetic lattice (cube with approximate dimensions of 14 × 14 × 14 mm 3 ) [9,10]. A CPU cooling fan including its aluminum cooler chassis was used as a fast-rotating object while a single blade of the fan was covered by lead to increase imaging contrast.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we have already shown that a split Hopkinson pressure bar (SHPB) instrumented with a high-speed camera can be used to assess the dynamic compressive response of various auxetic lattices manufactured by LPBF from 316L powdered austenitic steel [ 15 , 16 , 17 ]. The SHPB apparatus has also been used to evaluate the influence of elevated and reduced temperatures on the deformation response of steel auxetic lattices [ 18 ]. Furthermore, we have used modified Hopkinson pressure bar devices to investigate the dynamic impact characteristics of lattice structures [ 19 ] and metal foam-based lightweight cellular solids [ 20 ], where the possibility to use ex situ X-ray tomography has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%